2012
DOI: 10.1128/aem.07052-11
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Genetic Linkage Map Based on Amplified Fragment Length Polymorphism Markers and Development of Sequence-Tagged Site Markers for Marker-Assisted Selection of the Sporeless Trait in the Oyster Mushroom (Pleurotus eryngii)

Abstract: A large number of spores from fruiting bodies can lead to allergic reactions and other problems during the cultivation of edible mushrooms, including Pleurotus eryngii (DC.) Quél. A cultivar harboring a sporulation-deficient (sporeless) mutation would be useful for preventing these problems, but traditional breeding requires extensive time and labor. In this study, using a sporeless P. eryngii strain, we constructed a genetic linkage map to introduce a molecular breeding program like marker-assisted selection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…Several hypotheses have been proposed to explain distorted segregation, such as biased selection of SSIs, expression of lethal factors and unbalancing selection of mating-types (Larraya et al 2000;Foulongne-Oriol et al 2010). The mapped skewed loci appeared to locate together as segregation distortion regions in the genetic map, as previously reported in L. edodes (Terashima et al 2002), P. pulmonarius (Okuda et al 2009) and P. eryngii (Okuda et al 2012). The cluster distribution of skewed loci seemed to indicate that the segregation distortion of markers is most likely caused by genetic factors rather than statistical bias (Li et al 2010).…”
Section: Molecular Markers Used In This Studymentioning
confidence: 48%
See 1 more Smart Citation
“…Several hypotheses have been proposed to explain distorted segregation, such as biased selection of SSIs, expression of lethal factors and unbalancing selection of mating-types (Larraya et al 2000;Foulongne-Oriol et al 2010). The mapped skewed loci appeared to locate together as segregation distortion regions in the genetic map, as previously reported in L. edodes (Terashima et al 2002), P. pulmonarius (Okuda et al 2009) and P. eryngii (Okuda et al 2012). The cluster distribution of skewed loci seemed to indicate that the segregation distortion of markers is most likely caused by genetic factors rather than statistical bias (Li et al 2010).…”
Section: Molecular Markers Used In This Studymentioning
confidence: 48%
“…Genetic maps of several other edible mushrooms, including Agaricus bisporus (Kerrigan et al 1993;Callac et al 1997;Moquet et al 1999;Foulongne-Oriol et al 2010, Pleurotus ostreatus (Larraya et al 2000;Park et al 2006;Sivolapova et al 2012), Pleurotus pulmonarius (Okuda et al 2009) and Pleurotus eryngii (Okuda et al 2012), have been reported previously. For L. edodes, several molecular genetic maps are currently available.…”
Section: Introductionmentioning
confidence: 99%
“…Distorted segregation of markers has been commonly reported in linkage analysis (Manrique-Carpintero et al, 2016). The cluster distribution of skewed loci as SDRs has also been observed in other mushrooms, for example, A. bisporus (Foulongne-Oriol et al, 2010), L. edodes (Gong et al, 2014), and P. eryngii (Okuda et al, 2012). Several hypotheses such as the expression of lethal factors, biased selection of SSIs, and unbalanced selection of recognition loci have been used to explain distorted segregation of loci in fungi (Larraya et al, 2000;Foulongne-Oriol et al, 2010).…”
Section: Construction Of a High-dense Bin Mapmentioning
confidence: 94%
“…To date, only a few dozen genetic maps have been constructed for several widely cultivated mushrooms, including Agaricus bisporus (Foulongne-Oriol et al, 2010), Pleurotus spp. (Larraya et al, 2000;Okuda et al, 2009Okuda et al, , 2012Im et al, 2016;Gao et al, 2018), Lentinula edodes (Gong et al, 2016), and Auricularia auricula-judae (Lu et al, 2017). Most of the genetic linkage maps of edible mushrooms were generated using a few 10s to 100s of PCR-based markers (Foulongne-Oriol, 2012;Gong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic maps play an important role in the identification of QTLs and functional genes associated with economically-valuable traits in plants and animals [16]. In addition, genetic maps can be used to assemble sequences for genome sequencing, genome structure comparison, and marker-assisted selection (MAS) [17][18][19]. Previously, genetic map construction was primarily based on traditional molecular marker techniques, such as random amplified polymorphic DNA (RAPD), restriction fragment length polymorphism (RFLP), amplified fragment length polymorphism (AFLP), simple sequence repeat (SSR), and (inter-simple sequence repeat) ISSR [20][21][22].…”
Section: Introductionmentioning
confidence: 99%